Implementation of Pancasila Values Through School Culture - Nur Aminah Br Ginting (International Journal of Students Education, 2024)
This research aims to explore the implementation of Pancasila values through school culture in Indonesia. The Pancasila values, which are the ideological basis of the Indonesian state, such as justice, unity, democracy and humanity, are integrated into daily activities and practices in the school environment. The research method used in this article is systematic literature review, the author searches for published articles related to the topic determined by the researcher. The article search was limited to 30 articles and then 10 articles were selected which were deemed suitable to answer this research. The results of the research show that in implementing Pancasila values there are several obstacles, including the teacher's ability to motivate students, the lack of measuring tools for success, and the lack of synchronization between character education at school and at home. So there is a need for a sustainable system in forming Pancasila character for students. This research is aimed at understanding how Pancasila values are applied and practiced in schools